PARADIGMA PENDIDIKAN AGAMA ISLAM MULTIKULTURAL (STRATEGI MEMBANGUN HARMONI DI TENGAH POLARISASI SOSIAL) - Qoidul Khoir (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
Islamic Religious Education (PAI) plays a crucial role in shaping a society that is not only religious but also inclusive and tolerant. In addressing the increasing social polarization, a multicultural approach to PAI emerges as a strategic solution for fostering social harmony. This study examines the implementation of the multicultural PAI paradigm in Islamic educational institutions. A qualitative method with a case study approach was employed to explore the integration of multicultural values within the PAI curriculum through interviews, observations, and document analysis. The findings reveal that this approach enhances students' understanding of cultural and religious diversity while reducing prejudice and stereotypes. Despite challenges such as limited teacher understanding and parental resistance, this paradigm has proven effective in creating a more inclusive and harmonious generation. The integration of Islamic values, such as tawazun (balance), adl (justice), and ukhuwah insaniyah (human fraternity), into multicultural PAI offers an innovative solution for education in the globalization era. Thus, this paradigm has the potential to become a relevant and practical educational model in the context of Indonesia's pluralistic society.